HUBUNGAN ANTARA KEADILAN PROSEDURAL DAN KINERJA MANAJERIAL DENGAN PARTISIPASI ANGGARAN SEBAGAI VARIABEL INTERVENING - Ahmad Badaruddin Latief (Universitas Islam Nahdlatul Ulama Jepara, 2006)
AbstractThis study examines the intervening effects of Participation on the relationship between procedural justice and managerial performance Continuing research by Lou CM and Lim EW (2002), as for becoming object from this research is manufacturing business which located in Center of Java Indonesia.This research represent the empirical test which used convmience sampling technics in data collection. Data were collected using a sttrwy of 55 managers production, human resources, Finance and marketing from manufacturing organizations in Center of Java, Indonesia. Data analysis uses Path Analysis with the program SPss,.Result of hypothesis Examination indicate that three hypothesis are accepted. Hypothesis I (there are significance injluence between Procedural Justice to Budget Participation ). hypothesis 2 (there are significance injluence between Budget Participation to Managerial Performance). And hypothesis 3 (there are signtfwanc indirect influence between Procedural Justice to Performance Measurement through budget participation). Keywords: Procedural Justice, Budget Participation and Managerial Performanc.